Desain Sistem Informasi Pendukung Keputusan untuk Optimalisasi Profit pada Usaha Kecil Peternakan Broiler - Atris Suyantohadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2001)
Small Broiler Breeding Enterprise usually cultivates chicken from one hundred up to five thousand stocks. Some weakness were found in such enterprise including non market segmentation, unpredictable fluctuation on the price of the chicken, DOC and ransum. As the research object was Small Broiler Breeding Enterprise in Yogyakarta, which the sample was allocated on product of DOC Hibro Am 888. By using Decision Support Information System that was designed as a tool tor optimize profit of such enterprise, the best result of the sample analysis was achieved in seven week old. The result showed that for five hundred stocks, the optimum achievement should be Rp 574.508,1 at the production cost Rp 2.239.987,5 in November 2000. The Break Event Point analysis for 397 stocks. Basing on the selling price factor and its variable cost, the application program that was desugned for Decision Support Information System gave easiness in supporting the optimum decision.